Feasibility and user experience of augmented reality psychoeducation and mindfulness body scan for chronic low back pain - Robin Conen; Nikolai Hepke; Jörg Lohscheller; Steffen Mueller; Ana N. Tibubos; Ana N. Tibubos (Frontiers in Pain Research, 2025)
BackgroundChronic low back pain (CLBP) is prevalent and a multimodal therapy is indicated, including psychological treatment. Effective conventional treatments involve psychoeducation and mindfulness-based body scans, while virtual reality offers superior but temporary pain relief. Augmented Reality (AR), which combines conventional and virtual methods, is a novel therapeutic strategy.MethodsWe investigated the viability and acceptability of an AR intervention for CLBP by incorporating psychoeducation and mindfulness-based body scan techniques. 40 participants in two studies with a one-arm design underwent an educational AR intervention (Study I, n1 = 18) and an enhanced version with an additional body scan (Study II, n2 = 22). The studies focused on evaluating technical feasibility and multiple facets of user experience.ResultsThe results demonstrated high feasibility with low dropout rates (Study I: 10%, Study II: 0%). User experience ratings ranged from “Above Average” to “Excellent,” with the advanced intervention receiving higher ratings. While Study I showed no significant changes in affect pre- vs. post-intervention, Study II exhibited a significant reduction in negative affect and improved valence. Qualitative analysis provided insights into technical requirements and user perceptions.DiscussionThe AR prototype emerges as a promising psychoeducational tool for CLBP, aligning with current treatment guidelines and providing a basis for future controlled clinical trials. Limitations include the absence of a high-pain intervention group, as Study I reported a pain intensity of M = 1.05 and Study II reported M = 1.77 (Range: 0–10). Further research such as clinical trials with control groups is required to validate the efficacy of the piloted approach. The AR-based psychoeducation and mindfulness body scan intervention for CLBP demonstrated technical feasibility and a good user experience. Clinical Trial RegistrationOpen Science Framework.io; https://doi.org/10.17605/OSF.IO/DSW5X and https://doi.org/10.17605/OSF.IO/XVJBZ